A polarization light detector based on a multi-directional phase change array, a preparation method and a polarization light detection method
Patent Information
- Application Number
- CN202611024716.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]然而,这种依赖机械旋转部件的检测方案存在诸多固有缺陷
1、本发明通过机械剥离与干法转移技术结合构建了MoTe2/BP异质结偏振敏感光电探测器件,并在此基础上创造性地利用局域激光对2H相MoTe2表面进行灼烧使其发生相变,转化后的1T'相MoTe2具备优良的半金属导电特性,将其作为顶层接触通道与底层BP结合,极大地降低了金属电极(如铋/金电极)与BP半导体界面之间的接触电阻(Schottky势垒),有效提升了光生载流子的注入与提取速率;同时,本发明充分利用了底层黑磷(BP)薄膜本征的晶格褶皱结构及其带来的强烈面内光学各向异性(线性二向色性),将其作为核心光活性层,并结合异质界面的协同效应,使得该探测器不仅能覆盖宽光谱范围,更实现了对极化(偏振)光的高效、高敏感度探测,赋予了器件极短的光电响应时间和优异的探测率。
Smart Images

Figure CN122892274A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor devices, specifically relating to a polarization detector based on a multi-directional phase transition array, its fabrication method, and a method for detecting polarized light. Background Technology
[0002] Polarization detection has significant application value in micro-nano optoelectronic fields such as optical communication, target recognition, and remote sensing imaging. In many application scenarios, efficient and rapid detection of the polarization state of incident light is a core technical link in realizing functions such as information demodulation and target identification.
[0003] Currently, mainstream polarization detection methods heavily rely on external macroscopic optical components such as optical polarizers, waveplates, or analyzers. In practice, to obtain complete polarization information of unknown incident light, it is usually necessary to use a mechanical rotation device to drive the polarizer or the test stage carrying the sample to rotate sequentially at a specific angle, and record the photocurrent or light intensity response signal at each angle. Finally, the polarization direction information is extracted through data fitting.
[0004] However, this detection scheme relying on mechanically rotating components has several inherent drawbacks. First, the rotary motor and its associated precision transmission mechanism significantly increase the physical size and structural complexity of the detection system, hindering the miniaturization, portability, and on-chip system integration of optoelectronic devices. Second, the mechanical rotation process is accompanied by inertial delay and homing error, making the testing procedures cumbersome and the time required for a single complete measurement long, making it difficult to meet the real-time detection requirements for rapidly changing or transient polarization signals. Third, the mechanical moving parts inevitably experience fatigue wear after long-term repeated use, leading to a decrease in system accuracy and affecting the long-term stability and repeatability of the detection results.
[0005] In summary, existing polarization detection technologies are limited by the inherent bottlenecks of mechanical rotating components, making it difficult to meet the growing application demands in terms of integration, testing speed, and system reliability. Therefore, there is an urgent need to develop a novel solid-state polarization detection scheme that does not require mechanical rotating components. Summary of the Invention
[0006] To address the aforementioned technical problems, the present invention aims to provide a polarization detector based on a multi-directional phase transition array, a fabrication method, and a polarization detection method. By constructing a multi-directional encoded two-dimensional material local phase transition array, polarization angle information is cleverly mapped to spatial position information on a two-dimensional plane. Thus, under the condition of a fixed testing system, response signals at different positions can be obtained simply by moving the incident light spot, achieving polarization detection without mechanical rotation.
[0007] To achieve the above objectives, the present invention first provides a polarization detector based on a multi-directional phase transition array, comprising a substrate, a black phosphorus (BP) thin film disposed on the upper surface of the substrate, and a MoTe2 thin film disposed on the upper surface of the BP thin film. The MoTe2 thin film and the BP thin film form a heterojunction. The polarization detector further comprises a pair of electrodes disposed at both ends of the heterojunction. The MoTe2 thin film comprises a 2H-MoTe2 substrate and a plurality of 1T'-MoTe2 regions. The plurality of 1T'-MoTe2 regions are embedded in the 2H-MoTe2 substrate, and the plurality of 1T'-MoTe2 regions extend along a plurality of different preset directions, forming a multi-directional path-encoded local phase transition unit array.
[0008] In one embodiment of the invention, the plurality of different preset directions include at least three directions distributed at different angles relative to the BP's armchair crystal axis. These at least three directions are selected from any three or more directions within the set of 0°, 30°, 60°, 90°, 120°, and 150° angles relative to the BP's armchair crystal axis. Preferably, all or more of the included angle directions within the 0°, 30°, 60°, 90°, 120°, and 150° angles relative to the BP's armchair crystal axis can be selected.
[0009] In one embodiment of the present invention, the plurality of 1T'-MoTe2 regions are strip-shaped, and the width of each strip-shaped region is 10 μm to 40 μm.
[0010] In one embodiment of the present invention, the spacing between two adjacent 1T' phase regions in the plurality of 1T'-MoTe2 regions is 100 μm to 300 μm.
[0011] In one embodiment of the present invention, the thickness of the plurality of 1T'-MoTe2 regions is the same as the thickness of the molybdenum distelluride thin film.
[0012] In one embodiment of the present invention, the substrate is a silicon-based substrate, preferably a silicon wafer, and a 200-300 nm SiO2 layer is deposited on the substrate.
[0013] In one embodiment of the present invention, the black phosphorus film is a few-layer BP film with a thickness of 10-40 nm, and the MoTe2 film is a few-layer MoTe2 film with a thickness of 30-70 nm.
[0014] In one embodiment of the present invention, the electrode is a metal electrode, which includes a bismuth metal layer in direct contact with the BP thin film or the MoTe2 thin film and a gold metal layer deposited on the bismuth metal layer. The thickness of the bismuth metal layer is 4~10 nm and the thickness of the gold metal layer is 30~50 nm.
[0015] The present invention also provides a method for preparing the above-mentioned polarization detector, comprising the following steps: (1) The silicon substrate is ultrasonically cleaned and dried to obtain a clean silicon substrate; (2) The BP film and 2H-MoTe2 film obtained by mechanical peeling were sequentially transferred to the surface of a silicon substrate using PDMS dry transfer technology to obtain a BP / 2H-MoTe2 heterojunction; (3) The 2H-MoTe2 surface is locally burned by laser to induce a phase transition, and the laser scanning path is controlled to write directly along multiple different preset directions during the burning process to construct a multi-directional path encoded 1T'-MoTe2 local phase transition unit array. (4) Place the array structure obtained in step (3) on the photolithography stage, use photolithography to etch the device structure, and evaporate the electrodes to obtain a polarization detector based on a multi-directional phase transition array.
[0016] In one embodiment of the present invention, the ultrasonic cleaning step in step (1) includes first placing the silicon substrate in acetone for ultrasonic cleaning for 3-6 min, then transferring it to ethanol for ultrasonic cleaning for 3-6 min, and finally placing it in deionized water for ultrasonic cleaning for 3-6 min; after taking it out, it is dried with high-pressure nitrogen gas to obtain a clean silicon substrate.
[0017] In one embodiment of the present invention, in step (3), the wavelength of the laser used for laser ablation is 532~632nm, the power is 5~10 mW, and the single-point ablation time is 11~16 s.
[0018] In one embodiment of the present invention, step (4) of etching the device structure using photolithography specifically involves: placing the array structure on a maskless photolithography stage, aligning the electrode pattern with both ends of the entire heterojunction surface under a microscope, and using them as a pair of common electrodes to contact the MoTe2 thin film and the BP thin film respectively, exposing the area to be plated with electrodes, and blocking the heterojunction central channel area containing multiple local phase transition units, thereby obtaining the device structure using photolithography.
[0019] In one embodiment of the present invention, in step (4), the vapor deposition electrode comprises thermally vapor-deposited bismuth metal and thermally vapor-deposited gold metal; the vacuum conditions of the vapor deposition machine must meet 2×10 -3For Pa below 0.20~0.25 Å / s, the plating rate is 0.20~0.25 Å / s, the time required for thermal evaporation of bismuth metal is 3~8 minutes, and the thickness of the resulting electrode material is 4~10 nm; the time required for thermal evaporation of gold metal is 30~50 minutes, and the thickness of the resulting electrode material is 40~60 nm.
[0020] The present invention also provides an application of the above-mentioned polarization detector in polarization detection.
[0021] This invention also provides a method for polarized light detection using the aforementioned polarization detector, comprising the following steps: fixing the polarization detector on a stage, keeping the incident light path, optical polarization components, and stage stationary, using a microscopic optical path system (or a precision two-dimensional translation stage) to drive only the incident test spot to undergo microscopic displacement on a two-dimensional plane, so that it sequentially and precisely scans the local phase transition units with different preset coding directions on the polarization detector, and simultaneously using a Keithley test source meter to continuously collect the corresponding photocurrent response signals from the electrodes at both ends of the device, comparing the intensity of the collected photocurrent response signals of each local phase transition unit, and selecting the local phase transition unit with the largest absolute value of the output photocurrent. The preset coding direction of the physical space corresponding to this unit during device fabrication is directly determined as the polarization direction of the current incident light source.
[0022] Beneficial effects: 1. This invention constructs a MoTe2 / BP heterojunction polarization-sensitive photodetector by combining mechanical stripping and dry transfer techniques. Furthermore, it creatively utilizes localized laser ablation of the 2H phase MoTe2 surface to induce a phase transition. The resulting 1T' phase MoTe2 possesses excellent semi-metallic conductivity, which is used as the top-layer contact channel combined with the bottom BP layer. This significantly reduces the contact resistance (Schottky barrier) between the metal electrode (e.g., bismuth / gold electrode) and the BP semiconductor interface, effectively improving the injection and extraction rates of photogenerated carriers. Simultaneously, this invention fully utilizes the intrinsic lattice wrinkled structure of the bottom black phosphorus (BP) film and its resulting strong in-plane optical anisotropy (linear dichroism), using it as the core photoactive layer. Combined with the synergistic effect of the heterojunction interface, this allows the detector to not only cover a wide spectral range but also achieve highly efficient and sensitive detection of polarized light, endowing the device with an extremely short photoelectric response time and excellent detectivity.
[0023] 2. This invention utilizes laser path engineering technology to construct multiple 1T'-MoTe2 localized phase transition units with different directional characteristics on the same two-dimensional heterojunction surface, successfully achieving pre-coding of polarization direction information at the device level. This invention successfully fabricates a polarization detector by constructing an array of localized phase transition units with different preset directions on an optoelectronic device. When detecting the polarization angle of incident light, only the illumination position of the incident light spot needs to be changed to directly obtain the optical response in different polarization directions, completely realizing polarization detection without mechanical rotation, significantly improving testing efficiency and system stability.
[0024] 3. This invention is the first in the field of photoelectric detection to cleverly map the "polarization angle information" of the polarization dimension into "spatial position information" on a two-dimensional plane, realizing polarization detection based on position encoding. It fundamentally breaks the spatiotemporal physical limitations of traditional polarized light detection and provides a brand-new paradigm for on-chip polarization detection technology.
[0025] 4. The laser-induced localized phase transition process used in this invention has extremely high spatial resolution and excellent programmability. In actual device fabrication, phase transition unit arrays with arbitrary set directions such as 0°, 15°, 30°, 45°, 60°, 75°, and 90° can be flexibly designed and directly written according to specific polarization resolution requirements, exhibiting strong customizability and scalability.
[0026] 5. This invention achieves significant simplification in device structure. By constructing multiple phase-transition encoding regions within a single heterojunction channel and using only a pair of common electrodes for signal collection, the cumbersome process of fabricating complex microelectrode arrays necessary for multi-angle polarization detection is completely avoided. This not only greatly reduces the difficulty and manufacturing cost of photolithography alignment but also improves the optoelectronic integration of the single device. During testing, the light spot moves within the channel between the common electrodes, thereby exciting and reading the polarization response at different positions, truly achieving the most complex multi-dimensional polarization decoding with the simplest electrode structure. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the fabrication process of the BP / 1T'-MoTe2 heterojunction optoelectronic device in Example 1. (a) is a schematic diagram of a silicon substrate with a 285 nm SiO2 dielectric layer, (b) is a schematic diagram of a silicon-based BP heterojunction, (c) is a schematic diagram of a BP / 2H-MoTe2 heterojunction, (d) is a schematic diagram of the phase transformation of 2H-MoTe2 to 1T'-MoTe2 by laser ablation, and (e) is a schematic diagram of the device fabricated by using photolithography to create electrode patterns on both sides of the BP / 1T'-MoTe2 heterojunction and then thermally evaporating bismuth / gold electrodes onto the photolithographic patterns.
[0028] Figure 2The images show the physical images and comprehensive performance characterization diagrams of the optoelectronic device prepared in Example 1; (a) is a physical image of the BP / 1T'-MoTe2 heterojunction; (b) is the transient response curve of the device under 532 nm laser light; (c) is the polarization polar coordinate diagram of the Raman peak intensity ratio of the phase transition unit obtained by moving the light spot; and (d) is a comparison diagram of the Raman spectra of the local phase transition units with phase transition encoding directions at angles of 60° and 150° to the BP crystal axis, respectively.
[0029] Figure 3 The photocurrent step response diagrams for Example 1 at different wavelengths and optical powers are shown below; where (a) 460nm; (b) 520nm; (c) 640nm; and (d) 1064nm.
[0030] Figure 4 This is a schematic diagram of the structure of the multi-directional (0°, 30°, 60°, 90°, 120°, 150°) 1T'-MoTe2 local phase transition unit array constructed on the surface of the BP / 2H-MoTe2 heterojunction in Example 2.
[0031] Figure 5 The diagram shows a comparison of polarization testing methods, where (a) is the traditional mechanical rotation polarization testing method that relies on external components, and (b) is the mechanical rotation-free polarization testing method based on the spatial mapping of a moving light spot according to the present invention.
[0032] Figure 6 Raman spectra of 1T'-MoTe2 localized phase transition units in different directions.
[0033] Figure 7 The image shows the Raman polarization polar coordinates of the photodetector in Comparative Example 1 (single-element BP).
[0034] Figure 8 The image shows the Raman polarization polar coordinates of the photodetector in Comparative Example 2 (reverse stacking). Detailed Implementation
[0035] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explanation of the present invention and are not intended to limit the present invention.
[0036] Test method: AFM test: The sample is placed under the AFM (Brook Dimension Fastscan) probe and then scanned in semi-contact mode to obtain a surface topography image of the sample.
[0037] Angle-resolved Raman spectroscopy: In the spectral acquisition module of the computer software, set the parameters (select an 1800-line grating when measuring Raman), and set the spectrum measurement range to 100-500 cm. -1During the test, the sample stage was rotated to change the angle of the sample relative to the incident polarized light. Spectral data was acquired every 30° starting from 0° until the entire rotation cycle was covered. To avoid damaging the sample, the laser intensity was reduced to 1% during the test. Finally, the test was run and the files corresponding to each angle were saved to obtain the angular-resolved Raman spectral data of the sample.
[0038] Response speed test: To characterize the transient response performance of the device, a 532nm pulsed laser with a frequency of 1kHz was used to irradiate the device channel. The rapid changes in photocurrent over time were recorded using a test system. The rise time and fall time of the device were obtained by extracting the process of the photocurrent rising from 10% to 90% of its peak value and falling from 90% to 10%.
[0039] Raw materials used in the examples: BP and 2H-MoTe2 films were prepared by mechanical exfoliation. The specific steps were as follows: First, a portion of the sample was adhered to the surface of the BP crystal and the 2H-MoTe2 crystal respectively using 3M tape. Then, the tapes were peeled off from each other and repeated about ten times until the sample remaining on the tape was peeled off to an extremely thin thickness (BP was sky blue and MoTe2 was light white), thus obtaining the BP film and the 2H-MoTe2 film respectively. The peeled BP (or 2H-MoTe2) film was transferred to a silicon substrate (or a substrate with a BP film already transferred) using PDMS dry transfer technology. Subsequently, AFM testing was performed, and the thickness of the BP film was found to be 20 nm and the thickness of the MoTe2 film was 50 nm.
[0040] PDMS dry transfer technology: Apply a tape containing BP (or 2H-MoTe2) to the PDMS surface, let it stand for 1 hour, then peel off the tape, leaving a BP (or 2H-MoTe2) sample on the polydimethylsiloxane (PDMS) surface; then apply a clean silicon substrate (or a substrate with a BP film already transferred) to the PDMS surface, let it stand for another 10 minutes, then peel off the substrate, and the BP (or 2H-MoTe2) sample has been transferred to the substrate surface; the PDMS substrate used is self-prepared. To prepare it, first mix Dow Corning SYLGARD 184 silicone rubber and curing agent at a weight ratio of 10:1, stir evenly, wait until all bubbles disappear, then let it stand in a refrigerator at 4°C for 48 hours to solidify into a transparent film; The electrodes are prepared by vapor deposition, specifically including bismuth metal prepared by thermal vapor deposition and gold metal prepared by thermal vapor deposition; when performing thermal vapor deposition of bismuth metal and gold metal, the vacuum conditions of the vapor deposition machine must meet 2×10⁻⁶. -3For Pa below 0.20, the plating rate used is 0.20~0.25 Å / s; the time required for thermal evaporation of bismuth metal is 4 minutes, and the resulting electrode material thickness is 5 nm; the time required for thermal evaporation of gold metal is 35 minutes, and the resulting electrode material thickness is 50 nm.
[0041] Example 1 A method for fabricating a BP / 1T'-MoTe2 heterojunction optoelectronic device includes the following steps: (1) Substrate cleaning: A silicon wafer with a 285 nm silicon dioxide layer was used as the substrate. The substrate was placed in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning for 5 minutes each to remove surface organic matter. Then, it was dried with a high-pressure nitrogen gun to obtain a clean silicon substrate. (2) Material exfoliation: BP films with a thickness of 20 nm and 2H-MoTe2 films with a thickness of 50 nm were obtained by mechanical exfoliation technology; (3) Transfer of the underlying sample: The BP film stripped in step (2) is transferred to the clean silicon substrate surface in step (1) using PDMS dry transfer technology to obtain a silicon-based BP heterojunction; (4) Transfer of top layer sample: The 2H-MoTe2 film stripped in step (2) is accurately transferred to the BP film in step (3) using PDMS dry transfer technology to obtain BP / 2H-MoTe2 heterojunction; (5) Laser phase transition treatment: The 2H-MoTe2 surface in step (4) is locally burned with a laser with a wavelength of 532 nm and a power of 10 mW for 12 s to induce an irreversible phase transition and obtain a BP / 1T'-MoTe2 heterojunction. (6) Electrode and device fabrication: The BP / 1T'-MoTe2 heterojunction obtained in step (5) is placed on a maskless photolithography stage. Under a microscope, the electrode pattern is aligned with both ends of the heterojunction surface, contacting the 1T'-MoTe2 film and the BP film respectively, exposing the area to be plated with electrodes, while blocking the central area of the heterojunction. The device structure is obtained using photolithography. Then, the entire assembly is placed in a thermal evaporation chamber, where 5 nm of bismuth metal and 50 nm of gold metal are thermally evaporated sequentially (evaporation vacuum degree 2×10). -3 Below Pa, the evaporation rate is 0.20~0.25 Å / s. After the electrode is prepared, the BP / 1T'-MoTe2 heterojunction optoelectronic device is obtained.
[0042] The fabrication process of the device in Example 1 is as follows: Figure 1 As shown, Figure 2The figure shows the performance characterization of this optoelectronic device. As can be seen from the figure, under 532 nm pulsed laser testing, the device exhibits an extremely fast response speed, with rise and fall times of 85.4 μs and 61.3 μs, respectively (see Figure 1). Figure 2 b). Angular-resolved Raman spectroscopy revealed that this heterojunction device exhibits significant anisotropy, with a polarization ratio reaching 3.05 (see [link to data]). Figure 2 c).
[0043] Furthermore, the device exhibits a stable photocurrent step response in the 460nm to 1064nm wavelength range (see...). Figure 3 ).
[0044] Example 2 Since the device prepared by the method in Example 1 exhibits significant anisotropy for incident light at different angles, and the polarization ratio of the device is as high as 3 or more, this example constructs a polarization detector that can be used to quickly detect the polarization angle of incident light based on the performance of the above device. The preparation method of the polarization detector includes the following steps: (1) Substrate cleaning: A silicon wafer coated with a 285 nm silicon dioxide layer was used as the substrate. The substrate was placed in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning for 5 minutes each to remove organic matter on the surface. Then, it was dried with a high-pressure nitrogen gun to obtain a clean silicon substrate. (2) Material exfoliation: BP films with a thickness of 20 nm and 2H-MoTe2 films with a thickness of 50 nm were obtained by mechanical exfoliation technology; (3) Transfer of the underlying sample: The BP film stripped in step (2) is transferred to the surface of the clean silicon substrate in step (1) using PDMS dry transfer technology to obtain a silicon-based BP heterojunction; (4) Transfer of top layer sample: The 2H-MoTe2 film stripped in step (2) is accurately transferred to the BP film in step (3) again using PDMS dry transfer technology to obtain BP / 2H-MoTe2 heterojunction; (5) Laser path array encoding: The 2H-MoTe2 surface in step (4) is locally burned with a laser with a wavelength of 532 nm and a power of 10 mW. The burning time of a single point is 12 s, so that it undergoes an irreversible phase transition. During this process, the laser scanning path is controlled to write directly along the preset directions of 0°, 30°, 60°, 90°, 120° and 150° respectively, and a 1T'-MoTe2 local phase transition unit array containing 6 different direction encodings is constructed on the same heterojunction surface. The width of the 1T'-MoTe2 strip region in each preset direction is set to 20 μm, the number of burning points in the region is 5 (the burning points are spaced 3 μm apart), and the array spacing between two adjacent 1T' phase regions is set to 200 μm. (6) Electrode and Device Fabrication: The structure obtained in step (5) is placed on a maskless photolithography stage, and the electrode pattern is aligned with both ends of the entire heterojunction surface under a microscope. The electrode contact areas at both ends of the heterojunction are exposed using photolithography, while the central channel region of the heterojunction, which contains six locally encoded phase transition arrays in different directions, is masked and protected. The entire assembly is then placed in a thermal evaporation chamber and heated to 2×10⁻⁶ Å. -3 Under a vacuum level below Pa, 5 nm thick bismuth metal and 50 nm thick gold metal were sequentially thermally deposited at a deposition rate of 0.20–0.25 Å / s. After the electrodes were fabricated, a polarization detector based on a laser path-coded local phase transition array sharing a common pair of electrodes was obtained. The structure of the polarization detector, excluding the substrate and electrodes, is as follows: Figure 3 As shown, the blue arrow indicates the direction of BP's armchair crystal axis, the black dots indicate the laser ablation points, the white arrow indicates the 1T'-MoTe2 strip region, and 0°, 30°, 60°, 90°, 120°, and 150° represent the angles between BP's armchair crystal axis and the 1T'-MoTe2 strip region.
[0045] A method for detecting the incident angle of polarized light using the above-mentioned polarization detector includes the following steps: like Figure 5 As shown in (b), the polarization detector is fixed on the test stage. After the incident light passes through a polarizer to determine its polarization direction, it is then irradiated onto the polarization detector through the objective lens. When determining the polarization state of unknown incident light, the entire incident optical path, all optical polarization components, and the detector sample stage are kept completely stationary. Using a microscopic optical path system (or a precision two-dimensional translation stage), only the incident test spot is driven to undergo microscopic displacement on the two-dimensional plane, allowing it to sequentially and precisely sweep across the local phase transition units with different preset coding directions inside the heterojunction channel. As the spot moves and irradiates different phase transition units, the corresponding photocurrent response signal is continuously acquired from the common electrode at both ends of the device using a Keithley test source meter. Because each coding unit has a different strong anisotropic principal axis, its absorption and carrier excitation efficiencies for the fixed polarized light are also different, thus outputting a step-like photocurrent.
[0046] Taking the incident light test with an unknown polarization angle as an example, the Raman data of the light spot sequentially irradiating the local phase transition units at 0°, 30°, 60°, 90°, 120°, and 150° were measured. Figure 6 The comparison revealed a specific Raman characteristic peak (A) in the output of the 60° phase transition unit. 2g / A 1g When the intensity reaches its maximum, it can be determined that the polarization angle of the incident light is 60°.
[0047] To verify the accuracy of this judgment, a conventional mechanical rotation testing method was used to compare and verify the same device. Specifically, the incident light path and polarization state were kept completely unchanged. The test spot was fixed to illuminate a single test area (e.g., a 0° local phase transition unit) within the device, and the spatial position of the incident light spot was kept absolutely stationary. Then, the test stage was driven to rotate the entire device stepwise in the horizontal plane. Raman spectral response data of the local phase transition unit was continuously acquired every fixed rotation angle (e.g., 30°), and specific Raman characteristic peaks (A) at different mechanical rotation angles were extracted. 2g / A 1g The intensity was fitted to data in a polar coordinate system. Verification results show that the polar coordinate curve obtained by scanning and fitting using a traditional mechanical rotating stage also precisely points to 60° for the maximum Raman signal intensity. This underlying test data, obtained using the same device combined with a traditional standard physical rotation method, perfectly matches the judgment result directly obtained by the present invention through microscopic spatial position mapping, thus rigorously verifying the accuracy of the mechanical rotation-free polarization angle detection mechanism of the present invention.
[0048] Test results show that the moving spot detection method is effective for this device. With the incident light path and sample stage completely fixed, simply moving the test spot to sequentially illuminate the six coding units within the heterojunction channel allows direct extraction of response signals at different spatial locations and fitting of polarization polar coordinate diagrams. The testing process is free of mechanical delay and has a high detection speed.
[0049] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the MoTe2 stripping, transfer, and laser phase transition process in step (5) of Example 1 are omitted. That is, the 20 nm thick BP film obtained by stripping in step (2) is directly transferred to the surface of the silicon substrate, and then the photolithography and electrode evaporation in step (6) are directly performed. The remaining operations are completely consistent with Example 1 to obtain a photodetector based on elemental BP.
[0050] The obtained elemental BP photodetector and the heterojunction photodetector in Example 1 were tested, and the test results are as follows: Test results show that, although the elemental BP photodetector exhibits certain intrinsic polarization characteristics in the infrared band (such as...), Figure 7 As shown, its polarization ratio is only 2.14. Due to the lack of a built-in electric field at the heterojunction interface, the dark current is large, and photogenerated carrier recombination is severe. Its photoelectric response time is long, and its responsivity is much lower than that of the BP / 1T'-MoTe2 heterojunction device in Example 1 (polarization ratio 3.05). This shows that it is difficult for a single-element BP to simultaneously possess excellent carrier transport performance and fast photoelectric response.
[0051] Comparative Example 2 The order of thin film transfer and laser phase transition treatment in Example 1 was adjusted as follows: In step (3), a 50 nm thick 2H-MoTe2 thin film was first transferred to a clean silicon substrate surface using PDMS dry transfer technology; then, the 2H-MoTe2 on the substrate was locally burned using the laser parameters (wavelength 532 nm, power 10 mW, burn-off 12 s) in step (5) to induce a phase transition and obtain a 1T'-MoTe2 thin film; then, in step (4), a 20 nm BP thin film was transferred onto the phase-transformed 1T'-MoTe2 thin film to obtain a heterojunction with a 1T'-MoTe2 bottom layer and a BP top layer. The subsequent photolithography and electrode evaporation operations were completely consistent with those in Example 1 to obtain a photodetector.
[0052] The obtained photodetector was tested, and the results showed that although the reverse stacked structure exhibited certain polarization characteristics (such as...), Figure 8 As shown, its polarization ratio is 2.53, but its polarization sensitivity is still significantly lower than that of Example 1. More seriously, since the BP is located on the top layer and is directly exposed below the electrode, the metal electrode and the BP semiconductor form a large contact resistance, which prevents 1T'-MoTe2 from functioning as a low-resistance transport channel; at the same time, the BP exposed on the top layer lacks encapsulation protection, and its performance degrades rapidly during the fabrication and testing process. This proves that the process sequence of "bottom BP + top MoTe2 in-situ phase transition" in Example 1 plays a decisive role in improving device stability and carrier extraction efficiency.
[0053] Comparative Example 3 The same materials and processes as in Example 2 are used, but the "multi-directional" encoding process in step (5) is omitted. That is, during localized burning, the phase transition region is directly written on the heterojunction only along a single preset direction (such as 0°), and the remaining steps are completely the same to obtain a unidirectional encoded device.
[0054] Test results show that the moving spot detection method was also applied to this unidirectional device. The results indicate that, due to the lack of pre-encoding arrays in different directions across the entire device surface, the obtained polarization response angle remains singular regardless of the spot's position on the device. This method cannot achieve spatial mapping of the polarization angle dimension, making it impossible to determine the polarization state of unknown incident light.
[0055] Comparative Example 4 Traditional mechanical rotation polarization test (comparative test method): The single-directional polarization detector under test was fixed on the test stage. A self-built test optical path was used, with a continuous light source emitted from a laser. This light was sequentially modulated into linearly polarized light with a specific polarization state by a polarizer and a half-wave plate, and then focused by a microscope objective to precisely illuminate a single effective channel region of the device under test. A schematic diagram of the test is shown below. Figure 5 As shown in (a). After the test is started, the spatial position of the incident light spot on the device surface must be kept strictly constant. Instead, an external mechanical motor drives the half-wave plate (or the stage is rotated mechanically) to physically rotate in fixed angular steps (e.g., every 15° or 30°). At each rotation pause point, after the mechanical vibration stabilizes, the photocurrent data of the device at that specific polarization angle is recorded using a Keithley test source table. After the test is completed, the discrete photocurrent data points collected over a whole cycle (0°~360°) are extracted and fitted in a polar coordinate system to plot the relationship between photocurrent and polarization angle. This method relies entirely on macroscopic mechanical moving parts for angle traversal, resulting in long testing time and low system integration.
[0056] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A polarization detector based on a multi-directional phase transition array, characterized in that, The device includes a substrate, a black phosphorus (BP) film disposed on the upper surface of the substrate, and a MoTe2 film disposed on the upper surface of the BP film. The MoTe2 film and the BP film form a heterojunction. The polarization detector also includes a pair of electrodes disposed at both ends of the heterojunction. The MoTe2 film includes a 2H-MoTe2 substrate and multiple 1T'-MoTe2 regions. The multiple 1T'-MoTe2 regions are embedded in the 2H-MoTe2 substrate and extend along multiple different preset directions to form a multi-directional path-encoded local phase transition unit array.
2. The polarization detector according to claim 1, characterized in that, The plurality of different preset directions include at least three directions that are distributed at different angles relative to the BP's Armchair crystal axis, wherein the at least three directions are selected from any three or more directions in the set of 0°, 30°, 60°, 90°, 120° and 150° relative to the BP's Armchair crystal axis.
3. The polarization detector according to claim 1, characterized in that, The plurality of 1T'-MoTe2 regions are strip-shaped, with each strip-shaped region having a width of 10 μm to 40 μm. The spacing between two adjacent 1T' phase regions in the plurality of 1T'-MoTe2 regions is 100 μm to 300 μm.
4. The polarization detector according to claim 1, characterized in that, The substrate is a silicon-based substrate, on which a 200-300 nm SiO2 layer is deposited. The black phosphorus film is a few-layer BP film with a thickness of 10-40 nm. The MoTe2 film is a few-layer MoTe2 film with a thickness of 30-70 nm.
5. The polarization detector according to claim 1, characterized in that, The electrode is a metal electrode, which includes a bismuth metal layer in direct contact with the BP thin film or the MoTe2 thin film and a gold metal layer deposited on the bismuth metal layer. The thickness of the bismuth metal layer is 4~10 nm and the thickness of the gold metal layer is 30~50 nm.
6. The method for preparing a polarization detector according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) The silicon substrate is ultrasonically cleaned and dried to obtain a clean silicon substrate; (2) The BP film and 2H-MoTe2 film obtained by mechanical peeling were sequentially transferred to the surface of a silicon substrate using PDMS dry transfer technology to obtain a BP / 2H-MoTe2 heterojunction; (3) The 2H-MoTe2 surface is locally burned by laser to induce a phase transition, and the laser scanning path is controlled to write directly along multiple different preset directions during the burning process to construct a multi-directional path encoded 1T'-MoTe2 local phase transition unit array. (4) Place the array structure obtained in step (3) on the photolithography stage, use photolithography to etch the device structure, and evaporate the electrodes to obtain a polarization detector based on a multi-directional phase transition array.
7. The preparation method according to claim 6, characterized in that, The ultrasonic cleaning step in step (1) includes first placing the silicon substrate in acetone for ultrasonic cleaning for 3-6 min, then transferring it to ethanol for ultrasonic cleaning for 3-6 min, and finally placing it in deionized water for ultrasonic cleaning for 3-6 min; after taking it out, it is dried with high-pressure nitrogen gas to obtain a clean silicon substrate.
8. The preparation method according to claim 6, characterized in that, In step (3), the wavelength of the laser used for laser ablation is 532~632 nm, the power is 5~10 mW, and the single-point ablation time is 11~16 s.
9. The preparation method according to claim 6, characterized in that, In step (4), the device structure is etched using photolithography. Specifically, the array structure is placed on a maskless photolithography stage, and the electrode pattern is aligned with both ends of the entire heterojunction surface under a microscope. As a pair of common electrodes, they contact the MoTe2 thin film and the BP thin film respectively, exposing the area to be plated with electrodes. The heterojunction central channel area containing multiple local phase transition units is blocked, and the device structure is obtained using photolithography.
10. The application of the polarization detector according to any one of claims 1 to 5 in polarization detection.